Weighted Gene Co-Expression Network Analysis Identifies ANGPTL4 as a Key Regulator in Diabetic Cardiomyopathy via FAK/SIRT3/ROS Pathway in Cardiomyocyte - Dai, Lei; Xie, Yang; Zhang, Wenjun; Zhong, Xiaodan; Wang, Mengwen; Jiang, Hongcheng; He, Zhen; Liu, Xiaolei; Zeng, Hesong; Wang, Hongjie (Frontiers in Endocrinology, 2021)
Background: Diabetic cardiomyopathy (DbCM) is characterized by initial impairment of left ventricular relaxation followed by contractile dysfunction. Despite intensive research, the exact mechanism remains so far unsolved. Methods: We constructed weighted gene co-expression network analysis (WGCNA) to screen gene modules that were closely related with DbCM based on the GSE 5606 dataset, which contained expression data of the cardiac left ventricle in a rodent model of streptozotocin (STZ)-induced DbCM. Then, the most related hub gene, angiopoietin-like 4 (ANGPTL4), was selected for functional ex vivo and in vitro assays. In our experiments, STZ-induced diabetic mice (C57BL/6J) and human cardiomyocytes (AC16) were used to study the functional roles and potential mechanisms of ANGPTL4 in DbCM. Results: WGCNA analysis revealed the yellow and green modules were most correlated with DbCM, and identified ANGPTL4 as one of the most significantly upregulated hub genes (ANGPTL4, ACOT1, DECR1, HMGCS2, and PDK4). Consistent with the bioinformatic analysis, the amount of ANGPTL4 was significantly upregulated in diabetic mouse heart. DbCM group, compared with the control group, had increased phosphorylation of focal adhesion kinase (FAK), reduced SIRT3 expression, increased SOD2 acetylation, upregulated NADPH oxidase activation, elevated reactive oxygen species (ROS) produciton, and enhanced apoptosis in the diabetic mouse heart. Moreover, ANGPTL4 induced apoptosis via FAK/SIRT3/ROS pathway in human cardiomyocytes (AC16) under high glucose condition in vitro.These effects were abrogated by treatment of two independent siRNA for ANGPTL4, whereas exogenous recombinant ANGPLT4 protein treatment exacerbated those effects in AC16. Conclusion: We found ANGPTL4, ACOT1, DECR1, HMGCS2, and PDK4 were significantly increased in diabetic mouse heart. ANGPTL4 could promote cardiac apoptosis via a FAK/SIRT3/ROS dependent signalling pathway in DbCM.